Arab Spring and The Emergence of Anti-Shia Movement in Indonesia - Mochammad Maola (UIN Walisongo Semarang, 2020)
The rejection of Shia movement in Indonesia is a new discourse. Shia presence in Indonesia has been since the early arrival of Islam. But why the Shia resistance movement emerging in the early 21st century? I argue that the Arab spring is the biggest trigger is related to the rise of anti-Shia movements in Indonesia. This paper will explore the relationship between the Arab spring and its influence on the anti-Shia in Indonesia, including the emergence of a national-level organization called ANNAS, or Aliansi Nasional Anti Syiah (Anti-Shia National Alliance), which was declared on August 20, 2014. It aims to increase public awareness to the issue of anti-Shia and avoid potential conflicts which cause separations and threaten national stability as happened in the Arab countries that are currently happening provocations by parties who have interests and hidden agendas on them. Indonesia as a country that refer to Pancasila should be prepared for the issues that triggered the disintegration of the nation.